Test-beam measurements of instrumented sensor planes for a highly compact and granular electromagnetic calorimeter - Benhammou Yan (EPJ Web of Conferences)
The LUXE experiment is designed to explore the strong-field QED regime in interactions of high-energy electrons from the European XFEL in a powerful laser field. One of the crucial aims of this experiment is to measure the production of electron-positron pairs as a function of the laser field strength where non-perturbative effects are expected to kick in above the Schwinger limit. For the positron energy measurements and multiplicity spectra, a tracker and an electromagnetic calorimeter are foreseen. Since the expected number of positrons varies over five orders of magnitude, and has to be measured over a widely spread low energy background, the calorimeter must be compact and finely segmented. The concept of a sandwich calorimeter made of tungsten absorber plates interspersed with thin sensor planes is developed. The sensor planes comprise a silicon pad sensor, flexible kapton printed circuit planes for bias voltage supply and signal transport to the sensor edge, all embedded in a carbon fibre support. The thickness of a sensor plane is less than 1 mm. As an alternative, gallium arsenide sensors are considered with integrated readout strips. Prototypes of both sensor planes were studied in an electron beam of 5 GeV at DESY. Results from this test beam are presented on the sensor response homogeneity, edge effects, signal sharing and embedded trace effect.